The melodramatic public : film form and spectatorship in Indian cinema - Vasudevan, Ravi (New York : Palgrave Macmillan, 2011)
"What does it mean to say Indian movies are melodramatic? How do film audiences engage with socio-political issues? What role has cinema played in the emergence of new economic forms, consumer cultures, and digital technologies in a globalizing India? The Melodramatic Public analyzes melodrama as a narrative architecture and expressive form which connect the public and the private, the personal and the political, in ways that draw film audiences into complex passages of historical change. Vasudevan explores film form and narrative strategy across a wide repertoire of film traditions, including popular classics and canonical art works. Topics include the contemporary global moment associated with the category "Bollywood," changes in state policy and industrial organization, and the impact of digital technologies, new economies of consumption, and wider export markets on Indian film culture" --
Machine generated contents note: -- PART I: MELODRAMATIC AND OTHER PUBLICS * Shifting Codes, Dissolving Identities: Realist Art Cinema Criticism and Popular Film Form * The Politics of Cultural Address in a 'Transitional' Cinema * Neither State Nor Faith: Mediating Sectarian Conflict in Popular Cinema * A Modernist Public: The Double Take of Modernism in the Work of Satyajit Ray * PART II: CINEMA AND TERRITORIAL IMAGINATION IN THE SUBCONTINENT: TAMILNADU AND INDIA * Voice, Space, Form: the Symbolic and Territorial Itinerary of Mani Rathnams Roja (1992) * Bombay (Mani Rathnam, 1995) and Its Publics * Another History Rises to the Surface: Melodrama in the Age of Digital Simulation: Hey Ram! (Kamalahasan, 1999) * PART III: MELODRAMA MUTATED AND DIFFERENTIATED: NARRATIVE FORM, URBAN VISTAS AND NEW PUBLICS IN A HISTORY OF THE PRESENT * Selves Made Strange: Violent and Performative Bodies in the Cities of Indian Cinema 19742003 * The Contemporary Film Industry I: The Meanings of 'Bollywood.
Includes bibliographical references (p. [415]-436) and index.
Keywords: Motion pictures -- India; Melodrama in motion pictures; Motion pictures -- Social aspects -- India